Ethnobotanical Survey of Medicinal Plants Used Against Fungal Infections in Prefecture of Sotouboua Central Region, Togo - Teou Alfa; Kokou Anani; Yao Adjrah; Komlan Batawila; Yaovi Ameyapoh (European Scientific Journal, ESJ, 2018)
Plants are a major source of active ingredients and are for that fact used to treat many diseases such as fungal infections. The objective of this study was to identify the plants used in traditional medicine to treat fungal diseases in the prefecture of Sotouboua. An ethnobotanical survey was conducted among healers, elderly and knowledgeable villagers. A semi structured questionnaire and pictures showing common and easily recognizable fungal infection symptoms were used to support a live interview. During this study, 37 plant species belonging to 20 families have been identified. Fabaceae were the most represented family (7 species). The most used parts were leaves (43, 24%) followed by the roots (18, 91%). The decoction is the preferred method of preparation while the oral route is the main route of administration. Sotouboua prefecture in Togo has significant plant biodiversity that is used by dwellers in the management of fungal diseases.